Upaya Meningkatkan Hasil Belajar Kimia Materi Struktur Atom melalui Model Discovery Learning Siswa Kelas X-5 SMA Negeri 6 Mataram - Husniarti, Baiq Sri Ayu (Lembaga Yasin AlSys, 2023)
The purpose of this study was to determine the increase in learning outcomes in Chemistry on the subject of atomic structure through the Discovery Learning model for Class X-5 students of SMA Negeri 6 Mataram in the odd semester of the 2022/2023 academic year. This research method uses Classroom Action Research (CAR). The subjects of this study were all 32 students in class X-5 at SMA Negeri 6 Mataram in the odd semester of the 2022/2023 academic year. The instruments used were: observation sheets of teacher and student activities and the rubric of student creativity using percentage analysis. Based on the results of data analysis, it was obtained that: the Discovery Learning model can improve student learning outcomes in class X-5 Mataram 6 Public High School in the odd semester of the 2022/2023 school year. In the initial conditions, students who have completeness in learning Chemistry are 15 students or if the percentage is 46.88%. In the first cycle stage, there were 25 students or if the percentage was 78.13%, this proved an increase of 13.25% from the initial conditions. Then in the second cycle of students who are in complete learning Chemistry, there are 32 students or 87.50%. This proves an increase of 9.37% from cycle II.